2009
DOI: 10.1111/j.1651-2227.2008.01051.x
|View full text |Cite|
|
Sign up to set email alerts
|

Low‐carbohydrate (low & high‐fat) versus high‐carbohydrate low‐fat diets in the treatment of obesity in adolescents

Abstract: All diet regimens are associated with a significant reduction in BMI and improvement of some metabolic parameters in obese adolescents. Low-carbohydrate diets apparently have no advantage over high-carbohydrate low-fat diets. The significant drop in insulin level and HOMA in the low carbohydrate diet groups is noteworthy given the increasing frequency of type-2 diabetes as part of metabolic syndrome in children and youth. The impact of low carbohydrate diets in obese and insulin-resistant youth warrants furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 25 publications
5
86
0
1
Order By: Relevance
“…Reduced intake of dietary fat, particularly of saturated fat, is generally recommended as part of a healthy diet to reduce the risk of overweight and cardiovascular disease (Aggett et al, 1994). However, these recommendations have been debated (Silfverdal and Hernell, 2008;Demol et al, 2009), and were disputed in a recent study on 4-year olds, where low-fat intake seemed to be associated with an increased risk of overweight (Garemo and Strandvik, 2006;Garemo et al, 2007a). This study could not confirm the latter conclusion.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Reduced intake of dietary fat, particularly of saturated fat, is generally recommended as part of a healthy diet to reduce the risk of overweight and cardiovascular disease (Aggett et al, 1994). However, these recommendations have been debated (Silfverdal and Hernell, 2008;Demol et al, 2009), and were disputed in a recent study on 4-year olds, where low-fat intake seemed to be associated with an increased risk of overweight (Garemo and Strandvik, 2006;Garemo et al, 2007a). This study could not confirm the latter conclusion.…”
Section: Discussionmentioning
confidence: 67%
“…There is an ongoing debate whether low-carbohydrate, high-fat and high-protein diets should be recommended for children, rather than the current recommendation on low-fat and high-carbohydrate diets (Silfverdal and Hernell, 2008;Demol et al, 2009). In fact, it has been suggested that low-fat diets are associated with an increased risk of childhood obesity (Garemo and Strandvik, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The two trials, in obese adolescents, provide contradictory results of a low carbohydrate diet on BMI and total body fat changes as compared with high carbohydrate diets (Ebbeling et al, 2003;Demol et al, 2009). In one trial in 55 obese adolescents aged 12-18 years all dietary groups lost body fat, and changes in BMI, BMI-percentile or fat mass did not vary by diet group (Demol et al, 2009). All diets were equally effective in reducing body fatness as well as reducing insulin resistance and some fasting blood lipid measurements.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…Two randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate in relation to change in BMI and body fatness (Ebbeling et al, 2003;Demol et al, 2009).…”
Section: Cohort Studiesmentioning
confidence: 99%
“…Zu keinem Zeitpunkt gab es zwischen den beiden Gruppen signifikante Unterschiede in den anthropometrischen oder metabolischen Parametern. Es ist deshalb nicht überraschend, dass eine Metaanalyse zu dem Schluss kommt, dass es aktuell keine Evidenz dafür gibt, dass eine bestimmte Kostform für die Gewichtsreduktion adipöser Kinder und Jugendlicher signifikante Vorteile bringt [25].…”
unclassified